Biological control program is being developed for brown marmorated stink bug - J Lara; C Pickett; C Ingels; D Haviland; E Grafton-Cardwell; D Doll; J Bethke; B Faber; S Dara; M Hoddle (California Agriculture, 2016)
Brown marmorated stink bug (BMSB) is an invasive, polyphagous pest that has been detected in 42 U.S. states. In 2010, it caused millions of dollars in crop damages to apple growers on the East Coast, where it arrived from Asia during the 1990s. In 2002, BMSB was reported in California; since then, it has been detected in 28 counties and is established in at least nine counties. Although this pest has not yet been found on commercial crops in the state, detections of BMSB in commercial orchards have been documented in Oregon and Washington. Proactive research in California has joined national efforts led by U.S. Department of Agriculture researchers to develop a classical biological control program for BMSB. A study is under way to determine potential non-target effects of a specialist egg parasitoid, Trissolcus japonicus (Hymenoptera: Platygastridae), imported from Beijing, China, part of the home range of BMSB. In addition, the role of BMSB natural enemies residing in California is being assessed. A review of the recent research outlines the possible opportunities for reducing the threat BMSB poses to California.